ENT 530 Social Media Portfolio: Dough And Dust / Luqman Hakim Talib - Talib, Luqman Hakim (2021)
I really loves doughnuts and bomboloni that makes me want to establish Dough and Dust. I only focus on making bomboloni because majority of people love doughnuts with fillings inside it. Dough and Dust offer various types of bombolonis. The price is affordable and reasonable, as the products are high quality. It is suitable for breakfast, teatime, dinner and supper. We also have delivery our food from 9am until 10pm. We open order from Monday to Saturday only. We also open order for huge events and occasions. We market our business in the Facebook and WhatsApp. I only hire 2 employees with basic salary of RM1,000 which they will be my kitchen helper. We do not compromise our ingredients despite our bombolonis are sold at the cheaper price. For example, for the chocolate bombolonis, we are mixing our chocolate jam with Nutella spread to enhance the taste.